Taxonomic status of Choanoscolex lamothei García-Prieto, 1990 (Cestoda: Proteocephalidea) using morphological and molecular evidence - Scholz, Tomás; Rosas, Rogelio; Pérez-Ponce de León, Gerardo; Choudhury, Anindo; de Chambrier, Alain (The Journal of parasitology, 2003)
The taxonomic status of Choanoscolex lamothei, a proteocephalidean tapeworm described from the catfish Ictalurus meridionalis (= I. furcatus) from Oaxaca, Mexico, was evaluated on the basis of morphological examination of types and freshly collected specimens from the type host and partial sequences of the large subunit (28S) ribosomal DNA. This study revealed that C. lamothei is a species of Megathylacoides (Proteocephalidae: Corallobothriinae) because of the medullary position of the genitalia (entirely cortical in Choanoscolex), the presence of semispherical sphincters on the suckers, a follicular ovary, and the alternating position of the vagina. Megathylacoides lamothei n. comb. differs from congeneric species in lacking an apical organ and in the number (130-208) of testes. Molecular data confirm the position of M. lamothei within Megathylacoides, which contains species parasitizing ictalurid fishes in North America.
Keywords: nemoci ryb; Cestode Infections; DNA helmintů; DNA, Ribosomal; Phylogeny; RNA helmintů; Fish Diseases; Microscopy, Electron, Scanning; DNA, Helminth; zvířata; RNA, Helminth; fylogeneze; mikroskopie elektronová rastrovací; cestodózy; ribozomální DNA; Cestoda; Animals; Ictaluridae; RNA, Ribosomal, 28S; RNA ribozomální 28S